2008
DOI: 10.3892/ijmm.21.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromedin-U on immature rat adrenocortical cells: In vitro and in vivo studies

Abstract: Abstract. Neuromedin U (NMU) is a brain-gut peptide, that in the peripheral organs and tissues acts via a G protein-coupled receptor, called NMUR1. Reverse transcription-polymerase chain reaction showed the expression of NMUR1 mRNA in either cortex and medulla or dispersed zona glomerulosa and zona fasciculata-reticularis cells of the immature rat adrenals. Accordingly, immunocytochemistry demonstrated the presence of NMUR1-like immunoreactivity in the cortex and medulla of immature adrenals. NMU8 administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…In subsequent searches for mode of NMU action on corticosteroid secretion our group found that NMU had no effect on basal and ACTH-stimulated corticosterone secretion by freshly isolated or cultured inner zone adrenocortical cells, nor did it change their cytosolic Ca 2+ concentration (Malendowicz et al, 1994b; confirmed by Ziolkowska et al, 2008). However, this neuropeptide stimulated corticosterone output by adrenal slices, but not by fragments of adrenocortical autotransplants lacking medullary chromaffin cells (Malendowicz et al, 1994a).…”
Section: Nmu and Nms In The Hypothalamo–pituitary–adrenal Axis Functimentioning
confidence: 98%
See 1 more Smart Citation
“…In subsequent searches for mode of NMU action on corticosteroid secretion our group found that NMU had no effect on basal and ACTH-stimulated corticosterone secretion by freshly isolated or cultured inner zone adrenocortical cells, nor did it change their cytosolic Ca 2+ concentration (Malendowicz et al, 1994b; confirmed by Ziolkowska et al, 2008). However, this neuropeptide stimulated corticosterone output by adrenal slices, but not by fragments of adrenocortical autotransplants lacking medullary chromaffin cells (Malendowicz et al, 1994a).…”
Section: Nmu and Nms In The Hypothalamo–pituitary–adrenal Axis Functimentioning
confidence: 98%
“…In immature rat adrenal NMUR1 was expressed at both mRNA and protein (immunohistochemistry) levels while the signal from NMUR2 was absent. NMUR1 mRNA was detected in all adrenocortical zones and in medulla of the gland (Ziolkowska et al, 2008). Moreover, the presence of NMUR1 mRNA in isolated zona glomerulosa and fasciculata/reticularis cells rules out the possibility that the expression was due to the presence in the specimens assayed of the non-parenchymal components of the gland.…”
Section: Expression Of Nmu and Nms And Their Receptors In The Hypothamentioning
confidence: 99%
“…Method of culturing rat adrenocortical cells was described earlier [61]. Briefly, adrenals were obtained from 20 to 22 days old rats.…”
Section: Rat Primary Adrenocortical Cell Culturementioning
confidence: 99%
“…Details of primary adrenocortical cell culture were published previously (20)(21)(22)(23)(24)(25)(26)(27)(28). Briefly, for the preparation of one primary culture of adrenocortical cells, 12 rats were sacrificed by decapitation.…”
Section: Methodsmentioning
confidence: 99%